2020
DOI: 10.1002/alr.22740
|View full text |Cite
|
Sign up to set email alerts
|

Rhinologic disease and its impact on sleep: a systematic review

Abstract: Background Rhinologic disease can be responsible for systemic symptoms affecting mood, cognition, and sleep. It is unclear whether sleep disturbance in specific rhinologic disorders (chronic rhinosinusitis [CRS], rhinitis, and nasal septal deviation [NSD]) is an obstructive phenomenon or due to other mechanisms. In this review we examine the impact of CRS, rhinitis, and NSD on objective and subjective sleep outcome metrics and draw comparisons to normal controls and patients with known obstructive sleep apnea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 137 publications
(78 reference statements)
2
7
0
Order By: Relevance
“…Few studies focus on the Sleep‐SNOT subdomain alone. A recent systematic analysis demonstrated that for CRS patients, the Sleep‐SNOT is elevated to an average of 13.8 21 . The results of this study demonstrate higher mean Sleep‐SNOT scores for both OSA and non‐OSA patients.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Few studies focus on the Sleep‐SNOT subdomain alone. A recent systematic analysis demonstrated that for CRS patients, the Sleep‐SNOT is elevated to an average of 13.8 21 . The results of this study demonstrate higher mean Sleep‐SNOT scores for both OSA and non‐OSA patients.…”
Section: Discussionsupporting
confidence: 55%
“…Inflammatory mediators have been identified systemically in OSA patients, including IL's 1, 6 and 8, and TNF‐α; CRS shares many related cytokines in its pathophysiology 14,20 . Conversely, presence of obstructive and/or inflammatory rhinologic disorders has been shown to affect subjective and objective sleep metrics 21 . Inflammation or obstruction within the nose results in obligate oral breathing and can predispose patients to, or worsen existing OSA 13 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings also emphasize screening for these conditions and structuring care around both surgical reconstruction and cognitive-behavioural therapy, according to the patients' situation, through collaboration with specialists in sleep, psychiatry, and psychology, for optimal outcomes. Previous studies have demonstrated that rhinologic disorders such as nasal septal deviation, allergic rhinitis, and chronic rhinosinusitis have been shown to cause extensive sleep impairment (20) . Treatment of these rhinologic disorders may lead to clinically meaningful reductions in disease burden and improvements in both overall sleep quality and patient-reported fatigue (21) .…”
Section: Association Analysismentioning
confidence: 99%
“…The degree of impact of sinonasal disease on measures of sleep has long been acknowledged by patients and is oftentimes attributed to nasal congestion, but the degree of objective impact on sleep has been debated. To investigate this area, Fried et al 17 performed a systematic review with meta-analysis and demonstrated that CRS, rhinitis, and septal deviation were all associated with perturbations in sleep quality, but the obstructive component appeared mild. Further adding to this topic area, a multicenter prospective study by Little et al 18 demonstrated that objective sleep indices were not improved after ESS for CRS, despite improvements in patient-reported sleep quality and disease-specific QoL.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…The degree of impact of sinonasal disease on measures of sleep has long been acknowledged by patients and is oftentimes attributed to nasal congestion, but the degree of objective impact on sleep has been debated. To investigate this area, Fried et al 17 . performed a systematic review with meta‐analysis and demonstrated that CRS, rhinitis, and septal deviation were all associated with perturbations in sleep quality, but the obstructive component appeared mild.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%